Postural Dysfunction in Stroke Rehabilitation - Novitri Sumardi (Indonesian Journal of Physical Medicine & Rehabilitation, 2020)
ABSTRACTIntroduction: Trunk control ia a major part of postural control during human movement. This arecommonly affected in stroke but mostly are being overlooked compared to limb impairment. Thisarticle objective is to review the current literature on postural dysfunction after stroke and rehabilitationprinciples implementation.Method: Literature or data sources comprised through computer-aided search of published papers withthe key words of stroke or cerebrovascular accident, normal and pathological postural control, corestabilization exercise and trunk rehabilitation.Result: Thirty five papers were selected and were published from 2010-2 020.Conclusion: The abdominal muscles are held responsible to form a muscular c orset at the lumbar spineas proximal stabilization during any purposeful task. In stroke patients, the recruitment of posturalcontrol muscles is delayed with regard to the limbs activations. This will hamper the activities of dailyliving by disrupting the human postural adjustment mechanisms. The rehabilitation processes to regainpostural control are vital, and should involve exercises to imp rove trunk “core” muscle stability.Keywords: core stabilization, exercise, postural control, rehabilitation, stroke